Educational Intervention for Management of Acute Trauma Pain: A Proof-of-Concept Study in Post-surgical Trauma Patients - Colloca, Luana; Taj, Ariana; Massalee, Rachel; Haycock, Nathaniel R.; Murray, Robert Scott; Wang, Yang; McDaniel, Eric; Scalea, Thomas M.; Fouche-Weber, Yvette; Murthi, Sarah (Frontiers in Psychiatry, 2022)
Objective: Despite years of research and the development of countless awareness campaigns, the number of deaths related to prescription opioid overdose is steadily rising. Often, naive patients undergoing trauma-related surgery are dispensed opioids in the hospital, resulting in an escalation to long-term opioid misuses. We explored the impact of an educational intervention to modify perceptions of opioid needs at the bedside of trauma inpatients in post-surgery pain management. Methods: Twenty-eight inpatients with acute post-surgical pain completed this proof-of-concept study adopting an educational intervention related to opioids and nonpharmacological strategies in the context of acute post-surgical pain. An education assessment survey was developed to measure pre- and post-education perceptions of opioid needs to manage pain. The survey statements encompassed the patient's perceived needs for opioids and other pharmacological and nonpharmacological therapeutics to manage acute pain. The primary outcome was the change in the patient's perceived need for opioids. The secondary (explorative) outcome was the change in Morphine Milligram Equivalents (MME) used on the day of the educational intervention while inpatients and prescribed at the time of the hospital discharge. Results: After the educational intervention, patients reported less agreement with the statement, "I think a short course of opioids (less than 5 days) is safe". Moreover, less agreement on using opioids to manage trauma-related pain was positively associated with a significant reduction in opioids prescribed at discharge after the educational intervention. The educational intervention might have effectively helped to cope with acute trauma-related pain while adjusting potential unrealistic expectancies about pain management and, more in general, opioid-related needs. Conclusion: These findings suggest that trauma patients' expectations and understanding of the risks associated with the long-term use of opioids can be modified by a short educational intervention delivered by health providers during the hospitalization. Establishing realistic expectations in managing acute traumatic pain may empower patients with the necessary knowledge to minimize the potential of continuous long-term opioid use, opioid misuse, and the development of post-trauma opioid abuse and/or addiction. Keywords: Opioids, surveys, education, expectations, perceptions, trauma-related pain, post-operative monitoring